Advance in the characterization of alembic cachaça: ethyl lactate (Research, Society and Development, 2020)
In the current methodology for the analysis of cachaça, the limit of 200 mg/100 mL ethanol established in Brazilian legislation for the totality of esters present in cachaça is measured exclusively by the dosage of ethyl acetate, the principal ester in cachaça produced on an industrial scale (continuous distillation), whose asepsis procedures applied to the broth are focused on combating the activity of bacteria. However, it is known that producers of alembic cachaça (batch distillation) ferment the fresh juice, which naturally incorporates lactic bacteria from the environment. A survey of the analysis records of 300 samples, corresponding to 110 cachaça brands, was performed. The analyses were performed using the recommended laboratory methods and gas chromatography. The extensive occurrence of ethyl lactate was found in varying proportions, but with the same order of magnitude as ethyl acetate. It was concluded that, in addition to the olfactory peculiarities related to the particular contents in each brand, the simple presence of ethyl lactate (above a level that can be referred to as traces) permits one to infer whether the cachaça originates from alembic or from industrial production.